Disgust, Hate, and the Law - Manrique, Maria Laura (2024)
In this article, I cast doubt on the claim that disgust is the appropriate normative foundation of punishment with regard to hate crimes. Although traditional authors (Lord Devlin) have appealed to the emotion of disgust to justify punishment, recent approaches claim that disgust may not be considered as an illiberal strategy to justify punishment. I analyse one of the leading voices on this subject (Dan Kahan) and show why this view is flawed. Particularly, I demonstrate that even though disgust is a central emotion in how we come to understand some events, the disgust of the officials can never be used as a justification for punishment.